Rehabilitation diagnosis of patients with mine-explosive wounds of the lower leg based on the international classification of functioning, disability and health - Dorofieieva, O.E.; Yarymbash, K.S.; Glinyana , O.A.; Syomych, Yu.V.; Skrypchenko, I.T. (Medicni Perspektivi, 2023)
Mine-explosive wounds at the level of the lower leg are accompanied by significant functional disorders, leading to long-term disability, and in some cases – to disability. The introduction at the state level of the document of the International Classification of Functioning, Disabilities and Health (ICF) in the treatment and rehabilitation process of medical institutions, necessitates its detailed study and application for making a rehabilitation diagnosis of patients. The aim of this study is to improve the process of rehabilitation diagnosis of patients with mine-explosive wounds of the lower leg based on the International Classification of Functioning, Disability and Health. The study involved 54 people, the average age of the subjects was 37±4.2 years, 80% of them were men, 20% were women. In the course of the clinical and instrumental methods of examination of patients with mine-explosive wounds at the level of the lower leg, the assessment of categories according to the ICF revealed disorders at the level of structure: functions: s 75010 bones of lower leg, s 75012 muscles of lower leg, s 75013 ligaments and fasciae of lower leg, s 8104 skin of lower extremity; b 28015 pain in the lower limb, b 4550 general physical endurance, b 7101 mobility of several joints, b 7351 muscle tone of one limb, b 770 function of the stereotype of walking, b 7800 sensation of muscular stiffness, b 810 protective function of skin; activities: d 4104 standing position, d 4106 moving the center of gravity of the body, d 4501 walking long distances, d 465 moving using technical means, d 5100 washing body parts, d 5102 wiping and drying, d 5402 putting on footwear, d 5403 taking off footwear, d 5702 self-health support, d 850 well-paid work, d 920 recreation and leisure, e 1151 assistive products and technologies for personal everyday use, e 310 close relatives, e 355 professional health care workers. Mine-blast injuries of the shin cause impairments at the structural level, but the majority of impairments in patients were found at the level of function, activity, and participation, which significantly affected their quality of life.